Analysis Of Level Understanding Of The Accounting Students Towards The Management Accounting Course - Fitria Marisya; Hatidah Hatidah; Lestari Wuryanti; Muhammad Iqbal; R.A Rodia Fitri Indriani (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted at Darussalam Polytechnic on third semester students. For data collection using questionnaires, the questionnaire used must be valid and reliable to answer the understanding of accounting students towards the Management Accounting course. Validity is an index that indicates that the measuring instrument is measuring data correctly. The validity test can use the Pearson correlation technique for each number of the questionnaire score with the total score of the questionnaire. A questionnaire instrument is said to be valid if the correlation value is positive, and the probability value is less than the significant value (α 0.05). Cronbach's Alpha method is used to measure reliability in demonstrating that a questionnaire is maintainable and consistent, assuming that a questionnaire is said to be reliable if Cronbach's Alpha value is more than the r value of the table. Based on the results of the validity test related to accounting students' understanding of management accounting courses, it is explained that questionnaire instruments related to assets, liabilities, and equity are proven valid because they have a significant value on the validity test smaller than 0.05, while question instruments related to liabilities are not reliable.